The Effect of Giving Forest Guava Fruit Yogurt (Bellucia pentamera Naudin) on the Growth of Esterichia coli Bacteria in Mice (Mus musculus) - Shelly Festilia Agusanty; Maulidiyah Salim; Fara Chitra (Jurnal Penelitian Pendidikan IPA, 2025)
This research investigates the effect of forest guava fruit yogurt (Bellucia pentamera Naudin) on the growth of Escherichia coli bacteria in mice (Mus musculus). The study utilized an experimental design with treatment and control groups. Mice were divided into four groups: three treatment groups received forest guava fruit yogurt at concentrations of 5, 10, and 15%, respectively, administered at 0.5 ml per dose daily for 14 days, while the control group was given plain yogurt. E. coli growth was assessed by analyzing fecal samples from each group. The findings revealed that the growth of E. coli bacteria in the mice decreased significantly after administration of forest guava fruit yogurt, with the most pronounced reduction observed in the group receiving the 15% concentration. In contrast, the control group, which received plain yogurt, exhibited a less marked decrease in E. coli growth. These results suggest that forest guava fruit yogurt has a stronger inhibitory effect on E. coli bacteria compared to plain yogurt. In conclusion, forest guava fruit yogurt appears to be an effective natural agent for reducing E. coli growth in mice, potentially offering added health benefits beyond those of conventional yogurt.